Peningkatan Keterampilan Menulis Aksara Jawa Dengan Metode Field Trip Kelas Iv Sdn 01 Tanjang Kecamatan Gabus Kabupaten Pati Tahun Ajaran 2014/2015 - ROHMAH, WAHIDAH NUR, Drs. Mulyadi Sri Kamulyan, M.Pd (2015)
ABSTRACK Nur Wahidah Rohmah / A510100011. ENHANCEMENT OF JAVA AKSARA WRITING SKILLS WITH FIELD TRIP METHOD CLASS IV SDN 01 TANJANG DISTRICT OF CORK DISTRICT PATI 2014/2015. Thesis. The Faculty of Education, University of Muhammadiyah Surakarta. July, 2015. Environment is of paramount influence the learning process. However, in order to meet the curriculum, the learning has been confined in the classroom so that learning away from the neighborhood and felt less meaningful by the students. Required method capable invites students to leave the classroom, one of which is a method of learning field trip. This method is capable of eliminating the boredom of the students so that learning becomes more meaningful and able to provoke questions of students in terms of java script writing skills. The purpose of this research is to improve the writing skills of Java scripts by the method of the fourth grade field trip SDN 01 Tanjang District of Gabus Pati regency Year 2014/2015. This research is a classroom action research with qualitative approach. This classroom action research running three cycles. In the first cycle an increase in the average java script writing skills of 16.85 and 14.60 be categorized enough. In the second cycle back an increase in the average 18.95 java script writing skills and is categorized enough. In the third cycle a significant increase from the second cycle, namely with an average 21.05 java script writing skills and achieve success percentage above 80% so that the study was stopped in the third cycle.